Should euthanasia and assisted suicide be legal? : addressing key arguments and analyzing the consequences of legalization - Vargić, Hrvoje (Array, 2019)
The article examines whether countries should legalize euthanasia and assisted suicide. Firstly, context of the debate is provided by defining the key terms and giving the overview of how the debate evolved throughout history. The arguments in favor of legalizing euthanasia and assisted suicide are addressed, namely the argument from autonomy and self–determination and the claim for the “right to die with dignity”. The consequences which were showed to occur in the countries which legalized euthanasia and/or assisted suicide are analyzed, and the case study on the Netherlands and Belgium is made. Finally, the model for the dignity–respecting health–care is proposed followed by the call for bigger accessibility and funding for palliative care.